Sistem Buka-Tutup Sebuah Pintu Rumah Menggunakan Face Recognition Berbasis Mikrokontroler - Adi Chandranata; Laxsmy Devy; Reghina Alya Rihma (Syntax Literate, 2023)
Internet of Things technology is now widely used in all aspects of life including the application of smart homes. An automation technology is used to facilitate access at home, as well as access to the entrance of the house that uses facial image recognition (face detection). Human facial image recognition is one of the important technologies that continues to develop in the field of computer vision with its application in biometric recognition systems. One of them is by using the facial image recognition method, the Haar Cascade Classifier Algorithm. Therefore, a house door open-close system with facial recognition is designed using the ESP32-Cam module as a camera sensor. Face images were taken using the ESP32-Cam camera and processed using the ESP32 Microcontroller through the Arduino IDE program. Recognition results will be forwarded from the microcontroller to the PIR sensor, DC motor, buzzer, LED and website. The test result of this system is that if the detected face ID matches the data base, the PIR sensor will be active to detect the movement of objects in front of the entrance. When motion is detected, the buzzer as an alarm will be ON and the door will open and close automatically. If Face ID is not detected then the door will not open.